2013
DOI: 10.4070/kcj.2013.43.7.488
|View full text |Cite
|
Sign up to set email alerts
|

Intercoronary Communication between the Circumflex and Right Coronary Arteries Coexisted with Coronary Vasospasm

Abstract: Intercoronary arterial connection between normal coronary arteries is a rare variant of coronary anatomy in which there is open-ended circulation. It is distinguished from collaterals seen in the occlusive coronary artery disease. We report a case of bidirectional intercoronary communication between the left circumflex artery and the right coronary artery without occlusive coronary artery disease, but with left anterior descending artery spasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…It may play a protective role for myocardium if significant coronary artery stenosis or atherothrombosis develops in one of the two connecting vessels (10). On the other hand, myocardial ischemia can be resulted from a coronary steal, resulting in inadequate perfusion, particulaly when unidirectional flow is observed (2). There were only two cases in the literature similar to our case.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…It may play a protective role for myocardium if significant coronary artery stenosis or atherothrombosis develops in one of the two connecting vessels (10). On the other hand, myocardial ischemia can be resulted from a coronary steal, resulting in inadequate perfusion, particulaly when unidirectional flow is observed (2). There were only two cases in the literature similar to our case.…”
Section: Discussionmentioning
confidence: 53%
“…Coronary circulation's anomalies and variants are classified into four main groups; anomalies of origin, distribution, course and termination (1,4). Intercoronary communication or coronary arcade is a very rare coronary artery termination anomaly with unidirectional or bidirectional blood flow between two coronary arteries and is seen during coronary angiography in patients with or without coronary artery stenosis (5,6). The true Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, collaterals that develop in the presence of obstructive coronary artery disease are composed of endothelium supported by poorly organized collagen, muscle, and elastic fibers; in contrast, ICCs are similar to an epicardial vessel with a well-defined muscular layer. ( 10 ). Persistence of fetal coronary circulation has been suggested as the underlying mechanism for the development of ICC.…”
Section: Discussionmentioning
confidence: 99%
“…9 Intracoronary communications are a very rare subset of coronary artery anomalies with uni-or bidirectional blood flow between two or more coronary arteries. 10 These anomalies are mostly asymptomatic, however, clinical presentation in adults may result from myocardial ischaemia manifesting as angina, syncope, arrhythmias and even sudden death. 11,12 In our study, we found a communicating branch of the anterior interventricular artery was anastomosed with RCA on the anterior aspect of infundibulum.…”
Section: Discussionmentioning
confidence: 99%